Biofabricated macrophage and fibroblast membranes synergistically promote skin wound healing. Issue 3 (3rd June 2022) - Wang, Dongqing; Chen, Heying; Lei, Li; Chen, Jun; Gao, Jimin; Liu, Jiahe; Li, Qianyin; Xie, Yajun; Hu, Yi; Ni, Yilu
Abstract: Effective skin wound healing is a complex process involving anti‐inflammation, fibrosis, matrix reconstruction, and angiogenesis. This work aimed to integrate the macrophage‐mediated anti‐inflammation and fibroblast‐assisted matrix reconstruction for enhanced skin wound healing. Herein, we utilized the cytomembranes derived from repolarized M2 macrophages and fibroblasts to prepare the natural biologics. Results showed that the inflammatory M1 macrophages were repolarized to M2 phenotype by the M2 macrophage cytomembranes. As a consequence, the cytomembranes of M2 macrophage could facilitate the wound closure in mice. Furthermore, the addition of fibroblast membranes to the macrophage cytomembranes contributed to a better matrix reconstruction, neovascularization and angiogenesis. Next, we used a transforming growth factor‐β (TGF‐β) inhibitor to attenuate cutaneous scar formation. Therefore, our modality could promote skin wound healing and effectively suppress scar formation in the preclinical murine skin wounds. The cytomembrane biologics might provide a biocompatible and versatile tool for wound healing.